Determining Mediating Role of Managerial Commitment and Technological Capability Between Environmental Management Accounting and Organisational Efficiency: A Case of Middle Eastern Countries - Azam Ali (Arthatama, 2021)
The main aim of the following study is to investigate the mediating role of managerial commitment and technological capability between environmental management accounting (EMA) and organizational efficiency in the case of Middle Eastern countries. The data is mainly collected through primary sources. The questionnaire survey is developed and distributed among the non-financial listed organization firms established in 6 Middle Eastern countries through a web-based survey. The 6 Middle East countries selected for gathering data are Jordan, Saudi Arabia, Egypt, Qatar, Oman and Kuwait. Data is collected from 476 participants where the structural equation modelling (SEM) is conducted. The study’s results depicted that the EMA has a significant and positive effect on organizational efficiency. Moreover, both managerial commitment and technological capability were determined to have a significant and positive mediating role between EMA and organizational efficiency. Thus, the outcome of the study is that managerial and technological commitment plays a major role in EMA and organizational efficiency among Middle Eastern countries. Future studies can be conducted by targeting other countries such as Asian or European countries or using a qualitative approach such as interviews for gaining in-depth information.